THE EFFECTIVENESS OF SOCIODRAMA TECHNIQUES AS AN EFFORT TO OVERCOME BULLYING BEHAVIOR - ANGGUN PUTRI DEWANTARI SEMBIRING; ALI DAUD HASIBUAN (Universitas Islam Negeri Mataram, 2023)
In Indonesia, every year there is an increase in bullying cases, East Java is one of the provinces with bullying cases which continue to increase every year, this is reported from data recorded by KPAI (Indonesian child protection commission). This study aims to examine the effectiveness of the Sosiodrama technique in overcoming bullying behavior in class XII students at SMA Negeri 4 Tebing Tinggi. As a problem that often causes victims, bullying should get serious action. Bullying greatly affects the mental state of the individual who is the victim and even the individual or group of people who are the perpetrators as well. This study used a quantitative research method with two groupings of the experimental class and the control class. The resulting data were analyzed using the paired sample t-test. The resulting data shows that the pretest average score is lower than the posttest average score, so it can be seen that there is an increase in the effectiveness of the sociodrama technique in dealing with bullying behavior. The results of the research conducted obtained a significance of 0.012, which is smaller than 0.05, so Ho was rejected and Ha was accepted. From the acquisition of scores on the bullying behavior scale that were compared before and after the treatment was given, it showed a significant effect, so based on these results it was known that there was an influence of the Sosiodrama technique in overcoming bullying behavior of class VII-5 students of SMA Negeri 4 Tebing Tinggi.